Analisis Penguatan Kelembagaan Administrasi Kesehatan dalam Meningkatkan Prilaku hidup sehat bagi anak terlantar di Mataram - Chairun Nasirin (STIKES Mataram, 2015)
This study highlight the strengthening ofhealth administration ofthe health institution to improving the life quality regarding the_/uture implications to the health carejor the neglected children. The neglected phenomenon occurs due to the modern urban environment. No city like Mataram or even city anywhere in Indonesia is without the presence o/‘health problem ofneglected children. The data shows that in 2013, 78, 96 million children under the age of'l8 or 35percent of lndonesian population are need attentionfrom the health department. This is due to the children health were important role in improving the life quality ofthe children in the_ future.Key Words: Health Administration, Health Care, Neglected Children